Self-reported practices among traditional birth attendants surveyed in western Kenya: a descriptive study. Issue 1 (December 2016) - Bucher, Sherri; Konana, Olive; Liechty, Edward; Garces, Ana; Gisore, Peter; Marete, Irene; Tenge, Constance; Shipala, Evelyn; Wright, Linda; Esamai, Fabian
Abstract Background The high rate of home deliveries conducted by unskilled birth attendants in resource-limited settings is an important global health issue because it is believed to be a significant contributing factor to maternal and newborn mortality. Given the large number of deliveries that are managed by unskilled or traditional birth attendants outside of health facilities, and the fact that there is on-going discussion regarding the role of traditional birth attendants in the maternal newborn health (MNH) service continuum, we sought to ascertain the practices of traditional birth attendants in our catchment area. The findings of this descriptive study might help inform conversations regarding the roles that traditional birth attendants can play in maternal-newborn health care. Methods A structured questionnaire was used in a survey that included one hundred unskilled birth attendants in western Kenya. Descriptive statistics were employed. Results Inappropriate or outdated practices were reported in relation to some obstetric complications and newborn care. Encouraging results were reported with regard to positive relationships that traditional birth attendants have with their local health facilities. Furthermore, high rates of referral to health facilities was reported for many common obstetric emergencies and similar rates for reporting of pregnancy outcomes to village elders and chiefs. Conclusions Potentially harmful or outdated practices with regard to maternal and newborn care among traditional birth attendants in western Kenya were revealed by this study. There were high rates of traditional birth attendant referrals of pregnant mothers with obstetric complications to health facilities. Policy makers may consider re-educating and re-defining the roles and responsibilities of traditional birth attendants in maternal and neonatal health care based on the findings of this survey.